Effect of single L-carnitine dose over lactate production during high intensity-short volume effort - Martin, S. A.; Hadmas, R. M.; Graur, C. (International Journal of Applied Exercise Physiology, 2019)
Chronic oral ingestion of L-Carnitine can increase muscle carnitine and alter muscle metabolism during exercise. Yet, few similar results are published regarding acute oral ingestion and performance improvement. Our hypothesis is that non-mitochondrial ATP resynthesize is increased along with Carnitine acetylation, influencing lactate metabolism, and individual performance over single oral ingestion. Therefore, our propose will be to test the current hypothesis by monitoring performance indicators, during 30 seconds Squad Jump Test, after 4.5 g of L-Carnitine oral ingestion. Fourteen football players (n = 14) with a median age of 19 years old (18 -22), 71 kg (65 -74.5) median body weight of and 170.9 cm (168 -176.5) height were recruited in the study. Study protocol consisted of two 30 seconds Squad Jump Tests (SJT). The test were conducted before (Test 1) and after one single oral supplementation dose (4.5 g) with L-Carnitine (T2). Of the fourteen subjects (n = 14) all of them were allocated to L-Carnitine ingestion after T1 test. The ingestion consisted of 4.5 g/day. After 5 days the athletes re performed in T2 30 seconds SJT. To avoid circadian rhythm influence, similar conditions were respected. The statistical analysis were conducted by using SPSS 20. software. The level of significancewas set at a=0.05. Comparative changes were measured between T1 and T2. During T1, 1th rep, Tf was not significant different (p=1.00) from Tf, T2, 1th repetition, as seen through 0.43 (0.38-0.48) vs. 0.43 s (0.38-0.48) and 0.46 s (0.42-0.50) values. Similar data was observed during 1th repetition between Ct: 0.66 (0.58 -0.92) vs. 0.66 s (0.58 -0.92) (p=0.826). An improved performance can be unlikely due to L-Carnitine, as seen through Lactate accumulation. Further on, we must take into account a possibleeffect over Lactate tolerance which might favoured improved performance over T2unlike T1